1994
DOI: 10.1002/cne.903460104
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of gaze shifts in primates: Brainstem inputs to neck and extraocular motoneuron pools

Abstract: To determine whether there are brainstem regions that provide common input to the motoneurons that move both the head and the eyes, we injected wheat germ agglutinin-horseradish peroxidase complex (WGA-HRP) into neck motoneuron pools at spinal level C2 (N = 3) and extraocular motoneuron pools in the abducens (N = 1) and oculomotor/trochlear (N = 1) nuclei of rhesus and fascicularis macaques. We also injected WGA-HRP into spinal level C5-7 (N = 1) of a fascicularis macaque for comparison. After injections into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
72
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 70 publications
(77 reference statements)
10
72
1
Order By: Relevance
“…This observation suggests that in primates, the cFN output essentially influences an oculomotor stage for the control of gaze accuracy, i.e., a functional stage which is situated after that gaze-related commands are decomposed into premotor commands for moving the eyes in the orbit and premotor commands for moving the head. This hypothesis is consistent with an anatomical study showing that fastigial neurons projecting to the peri-abducens region are located more caudally than those projecting to the neck motoneurons pool in the upper cervical C2 (Robinson et al 1994). Thus the fastigial control of gaze shifts would involve different path-ways for controlling the eye and head components of gaze shifts.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…This observation suggests that in primates, the cFN output essentially influences an oculomotor stage for the control of gaze accuracy, i.e., a functional stage which is situated after that gaze-related commands are decomposed into premotor commands for moving the eyes in the orbit and premotor commands for moving the head. This hypothesis is consistent with an anatomical study showing that fastigial neurons projecting to the peri-abducens region are located more caudally than those projecting to the neck motoneurons pool in the upper cervical C2 (Robinson et al 1994). Thus the fastigial control of gaze shifts would involve different path-ways for controlling the eye and head components of gaze shifts.…”
Section: Introductionsupporting
confidence: 89%
“…This independent control of eye and head movements by the fastigial nucleus is also corroborated by results from two other studies. First, an anatomic study showed that fastigial neurons projecting to the peri-abducens region are located more caudally than those projecting to the neck motoneurons pool in the upper cervical C 2 (Robinson et al 1994). Second, during electrical microstimulation of the fastigial oculomotor region, saccadic eye movements were mostly evoked and rarely accompanied with head movements (Quinet and Goffart 2007).…”
Section: Fastigial Control Of Head-unrestrained Gaze Shiftsmentioning
confidence: 99%
“…In contrast to the PPRF data, stimulation of certain regions of the nucleus reticularis gigantocellularis (NRG) produces movements (Sprague and Chambers 1954;Quessy and Freedman 2004;Sasaki et al 2004) with an attenuated VOR gain (Quessy and Freedman 2004). The NRG resides caudal to the abducens nucleus (Peterson et al 1975;Tohyama et al 1979;Huerta and Harting 1982;Robinson et al 1994) and, compared to the PPRF, has a higher density of projections to the neck motoneurons (Tohyama et al 1979;Grantyn and Berthoz 1988). Quessy and Freedman (2004) assumed that they activated neurons within the pathway controlling only head movements and, therefore, interpreted the observed eye movement as VOR gain readout.…”
Section: Status Of the Vor Gain: Comparison With Previous Studiesmentioning
confidence: 99%
“…One possibility is that stimulation recruited fibers that traverse through the PPRF region and relay projections to the neck motoneurons (e.g., May and Porter 1992;Warren et al 2008). Another candidate is a subset of reticulospinal neurons that reside in the PPRF region Robinson et al 1994). Scudder et al (2002) proposed that long-lead burst neurons (LLBNs), which are intermingled with the EBNs, may be involved in controlling both eye and head movements.…”
Section: Effectors Controlled By Pprf Neuronsmentioning
confidence: 99%
“…Premotor neurons to the abducens and trochlear motor nuclei are also in the pontine reticular formation (699,1115,1344,1420). All three motor nuclei receive input from the vestibular nuclei as part of the vestibulo-ocular reflex (225,341,434,685,699,943,1051,1283). Some of these premotor neurons are GABAergic (superior vestibular nucleus) or cholinergic (the medial vestibular nucleus; Refs.…”
Section: B Afferent Projections To Orofacial Motor Nucleimentioning
confidence: 99%